Effect of oxytocin on haemodynamic change during caesarean section under spinal anaesthesia - A comparison between intravenous bolus or infusion technique - Murshid, Golam; Ali, Idris; Islam, Amirul; Yeasmeen, Sabina; Islam, Nurul; Sarkar, Nitai Chandra; Gafur, Azizul; Hye, Abdul (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Subarachnoid block for caesarean section is very acceptable technique and it rates are steadily increasing in recent years. It is now spreading up to remote areas. Infusion technique of oxytocin is safe during caesarean section under spinal anaesthesia. Objective To compare the haemodynamic changes caused by oxytocin given as an I/V bolus or infusion to decrease uterine bleeding in caesarean section. Method A total number of sixty patients ASA grade I were selected. Thirty patient in each group. In group A, parturient received oxytocin 5IU of I/V in bolus and group B, infusion of oxytocin 5IU diluted with 5ml normal saline given I/V over 2 min by using infusion pump. The study period was started just before oxytocin given and it was continued for a further 10 min. Systolic and diastolic BP, MAP, heart rate, uterine bleeding were recorded in every 1 min. Result The mean difference of all haemodynamic parameters at 2 to 5 mins of administration of oxytocin were statistically significant (p <0.05). Conclusion The haemodynamic changes were more marked in I/V bolus of oxytocin than infusion technique. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19801 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 48-51